BIO-DIESEL A MEAN TO SUSTAINABLE COMPETITIVE ADVANTAGE IN NIGERIA MANUFACTURING COMPANIES - Igandan, Ayodeji Omogbemi (My University, 2015)
In this era of re-engineering, sustainable competitive advantage cannot be achieved from outsourcing and constant innovation alone but through reduction in cost of production via introducing biodiesel. Globally, industries has experienced stunned economic growth from the recent global financial meet down of 2008, for sustainable competitive advantage to be achieved by industries ,a review of energy cost in production processes must be done. This research aim at reducing the cost of energy use in production processes through the introduction of biodiesel to industries in Nigeria .Discussion on operational strategy will be made to determine what strategy is been used by the case company, how to improving the strategy if right or adopting a new one if wrong. The methodology to be used are ‘SCA’ , Sense and Responds , ‘& AHP’ ,while data will be obtained through direct interview ,question naira and review of financial report of study case companies .The main outcome of this thesis is to substantiate the potential of energy management (biodiesel ) as a means to sustainable competitive advantage for industries in Nigeria. Keywords: Sustainable Competitive Advantage (SCA), Sense and Respond (S&R), Biodiesel, operation strategy, & AHP
Keywords: fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|